Does Metropolitan Area Management Matter in Brazil?: Elements of a Complex Issue. Issue 2 (2nd April 2016) - Vaz Guimarães de Araújo, Suely Mara; Fernandes, Antonio Sergio Araújo; Coêlho, Denilson Bandeira
Abstract: The article aims to discuss some crucial elements as regards metropolitan governance in Brazil in the current context. Some elements serve to explain the complexity of metropolitan governance in Brazil, one of which is the proliferated diffusion of metropolitan areas across the country after 1988, something that has not yet been properly explained. Some state governments have formalized metropolitan areas, aggregating few cities in underdeveloped regions without urban density. This has been done without technical criteria or clear political purpose. In addition, today's metropolitan issue requires an analytical treatment different to that used prior to democratization. In the current context, it requires not only the consideration of the federative challenge, but also the puzzle involving the many public policies that underlie the metropolitan space. It is necessary to observe the relevant actors in this 'game', particularly the strong Federal Government. Besides this, it is important to analyze what the Americans call 'marble cake': metropolitan plans and city master plans, urban mobility policy, sanitation policy, solid waste policy and other such imposed on urban areas by Brazilian law.